THE EFFECT OF TENS, US AND BALANCE EXERCISE AGAINST PATELAL FRACTURE IN THE ELDERLY: A CASE REPORT - Janani, Ummi Syarfina; Rahman, Farid; Arifin, Akhmad Zaenal (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Patellar fractures most often occur due to trauma, this condition often results in several problems such as pain, decreased muscle strength and decreased range of motion of the joint. The goal to be obtained is to know the effect of TENS, US and balance fatigue on reducing pain, increasing muscle strength and joint range of motion as well as increasing stability and balance in order to reduce risk factors for falls in patients with patellar fracture conditions . case presentation: A male patient aged 65 years in July 2019 had an accident, the accident occurred while driving a motor vehicle and was hit from behind. The patient fell and his right knee hit the barrier. The patient was immediately referred to the hospital for emergency treatment. Management and outcomes: Giving TENS and US modalities as well as balance and stability exercises its effectives for reduce pain, increase muscle strength, increase joint range of motion and improve stability and balance in patellar fractures. Discussion After fourth physiotherapy and exercise interventions were given, the results obtained were a decrease in motion pain and pressure from T1 to , an increase in muscle strength in the flexor knee from T1 with a muscle strength value of 4/5, an increase in muscle strength to 5/5 at T4, an increase in the range of motion of the joint on flexor knee at T1 the result is 950 and becomes 1150 at T4, and there is a decrease in risk factors for falling. Giving TENS and US modalities as well as balance and stability exercises can reduce pain, increase muscle strength, increase joint range of motion and improve stability and balance in patellar fractures. Conclusion:after given by physiotherapy modalities and exercise in patellar fracture it shows a good progression. The fourth physicaltherapy's treatment showed that there was an decrease in pain, improve the range of motion,increase muscle strength and reducing risk factors of fall.